Geger Muktamar NU ke-29 di Cipasung 1994 - Nur Fadilah Yusuf (Universitas Negeri Malang, 2022)
This article discusses the political intervention carried out by President Soeharto and the New Order government against the implementation of the Nahdlatul Ulama (NU) Congress when Kiai Abdurrahman Wahid (Gus Dur) was about to nominate himself as general chairman for the third term in 1994. This article also explains how the chronology of the feud between Gus Dur and the New Order government, so that the implementation of the 29th NU Congress in Cipasung became a national political contestation at stake. This article also discusses the role of President Soeharto and the New Order Government when campaigning ahead of the NU Congress by agitating and propaganda and preparing alternative candidates such as Abu Hasan. This study uses historical methods according to Louis Gottschalk, namely heuristics, source criticism, interpretation and historiography. In addition, the political approach is used in this article and the theory of power according to Hobbes is the analytical knife for the author in reconstructing this research. The purpose of the research results from this article is to review the past conflict between Gus Dur and the New Order Government, the political strategy carried out by President Soeharto and the New Order Government in the implementation of the 29th NU Congress in Cipasung and the importance of NU for the New Order Government and President Soeharto. in determining national policy.Artikel ini membahas tentang intervensi politik yang dilakukan oleh Presiden Soeharto dan Pemerintah Orde Baru terhadap pelaksanaan Muktamar Nahdlatul Ulama (NU) ketika Kiai Abdurrahman Wahid (Gus Dur) akan mencalonkan dirinya sebagai ketua umum untuk periode ketiga tahun 1994. Dalam artikel ini juga menjelaskan bagaimana kronologi dari perseteruan antara Gus Dur dengan Pemerintah Orde Baru, sehingga dalam pelaksanaan Muktamar NU ke-29 di Cipasung menjadi pertaruhan kontestasi perpolitikkan nasional. Artikel ini juga membahas mengenai peran Presiden Soeharto dan Pemerintah Orde Baru saat melakukan kampanye menjelang perhelatan Muktamar NU dengan melakukan agitasi dan propaganda serta menyiapkan calon alternatif seperti Abu Hasan. Penelitian ini menggunakan metode sejarah menurut Louis Gottschalk yaitu heuristik, kritik sumber, interpretasi dan historiografi. Selain itu, pendekatan politik digunakan dalam artikel ini dan teori kekuasaan menurut Hobbes yang menjadi pisau analisis bagi penulis dalam merekonstruksi penelitian ini. Tujuan hasil penelitian dari artikel ini yaitu mengulas mengenai konflik masa silam antara Gus Dur dan Pemerintah Orde Baru, strategi politik yang dilakukan oleh Presiden Soeharto dan Pemerintah Orde Baru dalam pelaksanaan Muktamar NU ke-29 di Cipasung dan pentingnya NU bagi Pemerintah Orde Baru dan Presiden Soeharto dalam menentukan kebijakan nasional.